2020
DOI: 10.1515/med-2020-0405
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the hub genes RUNX2 and FN1 in gastric cancer

Abstract: AbstractBackgroundThis study identified key genes in gastric cancer (GC) based on the mRNA microarray GSE19826 from the Gene Expression Omnibus (GEO) database and preliminarily explored the relationships among the key genes.MethodsDifferentially expressed genes (DEGs) were obtained using the GEO2R tool. The functions and pathway enrichment of the DEGs were analyzed using the Enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
(49 reference statements)
2
9
0
Order By: Relevance
“…RUNX2 promotes the development of multiple tumors such as prostate cancer and breast cancer and is a negative prognostic indicator of the survival of osteosarcoma. RUNX2, a mesenchymal stem marker [30], was reported by Chao Han et al that the high expression of RUNX2 and low expression of FN1 analyzed using the GEO2R tool could be the poor predictive marker of long survival in diffuse, poorly differentiated, and lymph node-positive GC [31]. Moreover, ZJ Guo et al also found that the levels of RUNX2 expression in gastric cancer tissues were correlated with the differentiation degrees, invasion depth and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 94%
“…RUNX2 promotes the development of multiple tumors such as prostate cancer and breast cancer and is a negative prognostic indicator of the survival of osteosarcoma. RUNX2, a mesenchymal stem marker [30], was reported by Chao Han et al that the high expression of RUNX2 and low expression of FN1 analyzed using the GEO2R tool could be the poor predictive marker of long survival in diffuse, poorly differentiated, and lymph node-positive GC [31]. Moreover, ZJ Guo et al also found that the levels of RUNX2 expression in gastric cancer tissues were correlated with the differentiation degrees, invasion depth and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 94%
“…Semmlinger et al, 2018;Shi et al, 2020;Zhang et al, 2021;. Moreover, these genes play an important role in the progression of several other cancers, for example, FN1 and CLEC5A have been reported to promote proliferation, invasion and metastasis of gastric cancer and glioblastoma (Fan et al, 2019;Han et al, 2020;Wang et al, 2020;Yang et al, 2019a). In line with other findings (Inoue et al, 2019;Milioli et al, 2017;Saatci et al, 2020), we also found a significant positive correlation between low expression of IL18 genes and good prognosis of breast cancer through survival curves, while high expression of FN1 and C3AR1 genes implied poor disease prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…FN1 expression is associated with OS in patients with gastric cancer. FN1 may serve as promising targets for gastric cancer treatment ( Han et al, 2020 ). miR-515-3p directly regulates MMP3 expression by binding to the coding sequence.…”
Section: Discussionmentioning
confidence: 99%